The best pooling strategy to reduce polymerase chain reaction tests during the coronavirus disease-19 pandemic at low prevalence - Chen-Lun Chu; Tai-Yin Wu; Sheng-Mou Hou; Kao-Shang Shih; Yo-Lun Chu; Cheng-Kuang Chen; Li-Wei Hung; Hao-Wei Hsu; Chen-Kun Liaw (Tzu Chi Medical Journal, 2025)
Objectives: Pooling can reduce reverse transcriptase polymerase chain reaction (RT-PCR) tests during the coronavirus disease-19 (COVID-19) pandemic. Pooling strategy is a complex issue. Recent advances in computer science may provide a better strategy. Materials and Methods: We developed our algorithm which can help healthcare workers set up their pooling policy during the COVID-19 pandemic. Results: Comparing with three other strategies, naming single pooling, array pooling, and hypercube pooling, our multiple pooling shows to be the best with minimal RT-PCR tests per patient. Conclusion: We hope clinicians in COVID-19 pandemic regions can use our algorithm to reduce both RT-PCR tests and time and hence save more lives.